PHYSICAL CHEMICAL TREATMENT OF WASTEWATER OF TEXTILE INDUSTRY - Salas Colotta, G. (2003)
A rapid and highly efficient treatment process for waste waters containing dye was investigated by combining the process of chemical coagulation/flocculalion. About 70% of DBO , DB05 and 80% of dyes was removed simultaneously.